Risk Factors for Dyspareunia After First Childbirth. Issue 3 (September 2016) - Alligood-Percoco, Natasha R.; Kjerulff, Kristen H.; Repke, John T.
Abstract : OBJECTIVE: To investigate risk factors for dyspareunia among primiparous women. METHODS: This was a planned secondary analysis using data from the 1- and 6-month postpartum interviews of a prospective study of women who delivered their first neonate in Pennsylvania, 2009–2011. Participants who had resumed sexual intercourse by the 6-month interview (N=2, 748) constituted the analytic sample. Women reporting a big or medium problem with painful intercourse at 6 months were categorized as having dyspareunia. Multivariable logistic regression was used to evaluate the effect of patient characteristics, obstetric and psychosocial factors, and breastfeeding on dyspareunia. RESULTS: There were 583 women (21.2%) who reported dyspareunia at 6 months postpartum. Nearly one third of those breastfeeding at 6 months reported dyspareunia (31.5%) compared with 12.7% of those not breastfeeding (adjusted odds ratio [OR] 2.89, 95% confidence interval [CI] 2.33–3.59, P <.001); 32.5% of those reporting a big or medium problem with perineal pain at 1 month reported dyspareunia at 6 months compared with 15.9% of those who did not (adjusted OR 2.45, 95% CI 1.93–3.10, P <.001); 28.3% of women who reported fatigue all or most of the time at 1 month reported dyspareunia at 6 months compared with 18.0% of those who reported fatigue less often (adjusted OR 1.60, 95% CI 1.30–1.98, P <.001); and 24.1% of those who scored in the upper third on the stress scale at 1 month reported dyspareunia at 6 months postpartum compared with 15.6% of those who scored in the lowest third (adjusted OR 1.55, 95% CI 1.18–2.02, P =.001). CONCLUSION: In this prospective cohort study, we identified specific risk factors for dyspareunia in primiparous women that can be discussed at the first postpartum visit, including breastfeeding, perineal pain, fatigue, and stress. Abstract : Risk factors for postpartum dyspareunia include breastfeeding, perineal pain, fatigue, and stress.